EFFECTS OF BLOCKAGE LOCATIONS FOR ENHANCED HEAT TRANSFER AND FLOW VISUALIZATION IN A TESTED DUCT WITH DUAL-INCLINED BAFFLES (DIB): A CFD ANALYSIS - Boonloi, Amnart; Jedsadaratanachai, Withada (My University, 2022)
Numerical analysis of fluid flow mechanism and heat transfer in a heat exchanger duct (HXD) with dual-inclined baffles (DIB) are reported. Three DIB types are examined: 1. “Type A” is located at the center of the HXD, 2. “Type B” is located on the upper-lower duct walls (as an orifice) and 3. “Type C” is a combination of the type A and B (as double orifices). The impacts of the ratio of DIB heights (b) to the square duct height (H; b/H) on increased heat transfer and friction loss are analyzed. Laminar flow (Re = 100 – 2000 based on the entry condition of the tested duct) is discussed. The simulated problems of the HXD equipped with various DIB types are analyzed by a commercial code (the finite volume method). To confirm accuracy results, the simulated domain of the HXD with the DIB is validated (optimum grid check and smooth duct validation). The simulated solutions are illustrated in terms of heat transfer and flow features. The performance assessments of the HXD with different DIB types are also presented in terms of thermal enhancement factor, Nusselt number and friction factor. It is interesting that the changed DIB position at an identical flow-blockage-ratio leads to the changed flow structure that impacts the variations of both the Nusselt number and pressure drop of the HXD. It is found that type C DIB provides the greatest thermal potentiality. The heat transfer rate of the HXD equipped with type A, B and C DIB is 1.38 – 13.93, 1.00 – 14.19 and 1.31– 14.45 times higher than that of the smooth duct, respectively, depending on the DIB height and Reynolds number. Additionally, the best thermal enhancement factor (TEF) of 4.04 is found for the HXD with the type C DIB at b1/H = 0.05 and b2/H = 0.15 at Re = 2000.
Keywords: Dual-inclined baffles; Heat exchanger duct; Heat transfer; Thermal enhancement factor; Vortex flow; Vortex generator